Lack of Public Knowledge About the Dangers of Dengue Fever in RT 19, Sawah Lebar Baru Subdistrict, Bengkulu City - Suryani, Ade Irma; Salma, Atika; Kartika, Dewi; Safitri, Devi; Hartati, Devi; Sari, Felia Novita; Sihombing, Ginna Veronica; Selviana, Indah; Sari, Nilam Kencana; Veronica, Syndi Ayu; Ningsih, Sunarti Maili; Yurnilawati, Yurnilawati; Novita, Vivin; Putri, Anisa Ika (Jurnal Inovasi Kerja Nyata, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. Although prevention efforts have been intensified, public awareness and understanding of DHF remain low, especially in densely populated areas such as Neighborhood Unit (RT) 19 in Sawah Lebar Baru Village, Bengkulu City. This study aims to determine the level of public understanding of DHF and the factors influencing it. The research method used was quantitative descriptive with a survey approach. Data collection was conducted through questionnaires distributed to 20 respondents. The results showed that the majority of the community had low knowledge about the causes, symptoms, transmission methods, and prevention of DHF. Lack of socialization, low education levels, and insufficient attention to environmental cleanliness were the main contributing factors. The conclusion of this study is the need to enhance public education through regular counseling programs conducted by health workers and Posyandu cadres.